Analysis of The Need for Electronic Teaching Materials on the Topics of Relations and Function for Grade VIII - Unika Tri Pangestuti; Dwi Sulistyaningsih; Eko Andy Purnomo (Universitas Cokroaminoto Palopo, 2025)
Teaching materials are an essential component in conveying knowledge to students during the learning process. The optimal use of teaching materials can be achieved if they are designed according to the characteristics and needs of the students. This study aims to analyze the need for electronic teaching materials on the topic of relations and functions that align with student characteristics, as well as to serve as a reference in developing effective electronic-based mathematics teaching materials to enhance students' learning motivation. This research is qualitative in nature, using a descriptive qualitative research method. The research subjects are eighth-grade students and mathematics teachers at a public junior high school in Purbalingga Regency. The research instruments include the researcher, observations during the learning process, a student needs analysis questionnaire validated by content experts, and interview guidelines for both students and mathematics teachers. The stages of analysis involve data collection, reduction, presentation, and drawing conclusions. Based on the research findings, it can be concluded that the use of electronic teaching materials on relations and functions is crucial to meet students' learning needs. This study is expected to serve as a reference in the development of electronic teaching materials on the topic of relations and functions in the future.